The effect of locations of triple bond at terphenyl skeleton on the properties of isothiocyanate liquid crystals. Issue 9 (15th July 2017) - Li, Juanli; Li, Jian; Hu, Minggang; Che, Zhaoyi; Mo, Lingchao; Yang, Xiaozhe; An, Zhongwei; Zhang, Lu
ABSTRACT: Three series of new tolanyl benzene isothiocyanate liquid crystalsA, B andC were synthesised with lateral fluorine substituent at different positions and 3, 5-difluoro terminal groups. SeriesD and compoundE4 with carbon–carbon triple bond connected with the isothiocyanated benzene were also prepared as reference. Their structures were confirmed using infrared spectrometry, nuclear magnetic resonance and mass spectrometry. The mesomorphic properties, birefringence, dielectric anisotropy and miscibility of these compounds were investigated. SeriesA exhibits higher clearing points than that of the corresponding compoundsD . SeriesB displays the lowest melting points, the broadest nematic phase temperature range and no smectic phase with increase of the carbon number of alkyl chain. Lateral fluorine in the position of Y (seriesC ) results in an increase of smectic phase. The birefringence ( 0.454–0.490) of seriesA is almost the same as that of the corresponding reference compoundsD, while seriesB shows a decrease of Δ n about 0.05 compared with compoundsD . For comparison, mixtures formulated byA andB exhibit higher clearing points and better low temperature stability than those of the mixtures based compoundsD in the same fraction. Graphical Abstract: